2017
DOI: 10.1387/ijdb.160308od
|View full text |Cite
|
Sign up to set email alerts
|

Functional differences between Tcf1 isoforms in early Xenopus development

Abstract: In Xenopus gastrula stage embryos, four isoforms of Tcf1 (B, C, D and E) are present with high amino acid sequence conservation compared to fish, mice and human. We studied possible functional differences between these Tcf1 isoforms during early Xenopus development. After overexpression of single Tcf1 isoforms, two distinct phenotypes were observed. Overexpression of the B or D isoforms of Tcf1, which both lack a C-clamp, enhances early canonical Wnt signaling and induces ectopic dorsal mesoderm at the expense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We found that the WRE located in the proximal region of GRE1 within the chrd(-2250) promoter was critical for the Gsc-mediated activation of chrd transcription. Previous studies have reported that Tcf7 induces chrd expression in Xenopus embryos [ 27 , 28 ]. Additionally, a recent study demonstrated that the active Wnt/β-catenin signaling-mediated induction of organizer genes requires two steps [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the WRE located in the proximal region of GRE1 within the chrd(-2250) promoter was critical for the Gsc-mediated activation of chrd transcription. Previous studies have reported that Tcf7 induces chrd expression in Xenopus embryos [ 27 , 28 ]. Additionally, a recent study demonstrated that the active Wnt/β-catenin signaling-mediated induction of organizer genes requires two steps [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results support those of previous reports, wherein ectopic Tcf7 robustly induces chrd expression in Xenopus [ 28 ]. However, different Tcf7 isoforms show functional differences in activating organizer-specific genes and producing distinct Xenopus phenotypes [ 27 ]. We observed that Tcf7 recognizes only the WRE site, suggesting that Wnt/Tcf signaling activates organizer-specific genes, such as chrd, by binding to conversed cis-acting elements [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation